2013
DOI: 10.1111/bju.12065
|View full text |Cite
|
Sign up to set email alerts
|

Survival after radical prostatectomy for clinically localised prostate cancer: a population‐based study

Abstract: We present the first survival analysis of a complete, nationwide cohort of men undergoing RP for localised prostate cancer. The main limitation of the study was the relatively short follow-up. Interestingly, our national results are comparable to high-volume, single institution, single surgeon series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…The first patient who had a radical prostatectomy was in 1995, since then the management of patients has rapidly evolved reaching an equivalent level with the rest of the European community [12]. The aim of this study was to elucidate the incidence and mortality among elderly patients with prostate cancer in the period from 1980 to 2012, covering the introduction of curative treatment, the extended use of prostate-specific antigen (PSA) in pseudoscreening and change of the Gleason graduation [13].…”
mentioning
confidence: 99%
“…The first patient who had a radical prostatectomy was in 1995, since then the management of patients has rapidly evolved reaching an equivalent level with the rest of the European community [12]. The aim of this study was to elucidate the incidence and mortality among elderly patients with prostate cancer in the period from 1980 to 2012, covering the introduction of curative treatment, the extended use of prostate-specific antigen (PSA) in pseudoscreening and change of the Gleason graduation [13].…”
mentioning
confidence: 99%
“…In all cases of death, national electronic patient files, discharge letters and the National Danish Pathology Register were reviewed to confirm the cause of death. The complete list of causes of death has recently been published [6].…”
Section: Methodsmentioning
confidence: 99%
“…The authors of this study recently reported causes of death and survival among Danish patients with localized PCa who had undergone RP during the past 16 years [6]. In the present study, an in-depth analysis of these data was undertaken by comparing mortality and survival to a cohort in the general Danish population, matched for age and date of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 A large-scale Danish study of radical prostatectomy conducted in 6489 men with localised prostate cancer, including 1818 men with high-risk disease, reported good outcomes at 15 years (Table 1). 9 Additional support for the use of radical prostatectomy in high-risk prostate cancer patients comes from the Cancer of the Prostate Strategic Urologic Research Endeavor (CAPSURE) registry of 7538 men. 10 Results from the study indicated that radical prostatectomy was associated with a significant and substantial reduction in mortality relative to radiation therapy and to androgen deprivation therapy as monotherapy.…”
Section: Improving the Surgical Treatment Of High-risk Localised Or Lmentioning
confidence: 99%